Optical laminate and image display device

By optimizing the polarizer thickness and the storage elastic modulus ratio of the pressure-sensitive adhesive layer in the optical laminate, the problem of display inhomogeneity in high temperature environments is solved, and a more stable image display is achieved.

CN119439347APending Publication Date: 2025-02-14NITTO DENKO CORP
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
CN202411036613.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-07-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing optical laminates may cause unevenness in display of the image display device under high temperature environments.

Method used

An optical laminate is designed, including a polarizer of the polarizer, a first retardation layer, a second retardation layer and a pressure-sensitive adhesive layer to ensure the thickness T of the polarizer and the storage elasticity of the pressure-sensitive adhesive layer. The modulus E satisfies the ratio of T/E≤0.100 (μm/kPa), and the shrinkage rate after heating at 85°C for 240 hours is controlled to 0.80% or less.

Benefits of technology

By optimizing the structure of the optical laminate, the display unevenness of the image display device in a high temperature environment can be effectively suppressed, and the display stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119439347A_ABST
    Figure CN119439347A_ABST
Patent Text Reader

Abstract

Provided is an optical laminate that can suppress display unevenness in a high-temperature environment when applied to an image display device. An optical laminate according to at least one embodiment of the present invention comprises, in the stated order: a polarizing plate including a polarizer; a first retardation layer; a second retardation layer; and a pressure sensitive adhesive layer. The first retardation layer and the second retardation layer are each a liquid crystal alignment fixing layer, and a thickness T of the polarizer and a storage elastic modulus E of the pressure-sensitive adhesive layer satisfy the following relationship: T / E < = 0.100 ([mu] m / kPa).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an optical layered body and an image display device. Background Art

[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices or inorganic EL display devices) have rapidly gained wider applications. In image display devices, optical laminates including delay films (e.g., anti-reflection films obtained by integrating polarizers and delay films with each other) have been used in many cases. In recent years, with the increase in demand for thinning of image display devices, the demand for thinning of optical laminates has also increased. In order to thin the optical laminate, the thinning of the delay layer (delay film) that has a large contribution to the thickness has made progress. A typical example of a delay film is a film obtained by orienting a liquid crystal compound and fixing the orientation state (hereinafter referred to as a "liquid crystal film"). The birefringence (Δn) of the liquid crystal compound is much greater than the birefringence of the resin, so the thickness of the liquid crystal film used to obtain the desired in-plane delay can be made much smaller than the thickness of the stretched film of the resin film. However, when an optical laminate using a liquid crystal film is applied to an image display device, display non-uniformity may increase under a high temperature environment. Summary of the invention

[0003] The present invention has been made to solve the above-mentioned problems of the prior art, and a main object of the present invention is to provide an optical laminated body capable of suppressing display unevenness in a high temperature environment when applied to an image display device.

[0004] The optical laminate according to at least one embodiment of the present invention includes, in the order described: a polarizing plate including a polarizer; a first retardation layer; a second retardation layer; and a pressure-sensitive adhesive layer. The first retardation layer and the second retardation layer are each a liquid crystal orientation fixing layer, and the thickness T of the polarizer and the storage elastic modulus E of the pressure-sensitive adhesive layer satisfy the following relationship:

[0005] T / E≤0.100(μm / kPa).

[0006] In the above item [1], the sum of the shrinkage rate of the optical laminate in a first direction and the shrinkage rate in a second direction perpendicular to the first direction after heating at 85° C. for 240 hours is 0.80% or less.

[0007] In the above item [1] or [2], the storage elastic modulus E of the pressure-sensitive adhesive layer is 70 kPa or more, and / or the thickness T of the polarizer is 8 μm or less.

[0008] In any one of items [1] to [3] above, the first delay layer has Re (550) of 200nm to 300nm, and its slow axis forms an angle of 10° to 20° with the absorption axis of the polarizer; and the second delay layer has Re (550) of 100nm to 190nm, and its slow axis forms an angle of 70° to 80° with the absorption axis of the polarizer.

[0009] In any one of the above items [1] to [4], the optical laminate further includes a third retardation layer having a refractive index characteristic showing a relationship of nz>nx=ny between the polarizing plate and the pressure-sensitive adhesive layer.

[0010] According to at least one embodiment of the present invention, there is provided an image display device comprising the optical laminated body according to any one of the above items [1] to [5].

[0011] According to at least one embodiment of the present invention, an optical laminated body that can suppress display unevenness in a high temperature environment when applied to an image display device can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 is a schematic cross-sectional view of an optical stack according to at least one embodiment of the present invention. DETAILED DESCRIPTION

[0013] Typical embodiments of the present invention are described below. However, the present invention is not limited to these embodiments.

[0014] (Definition of terms and symbols)

[0015] Definitions of terms and symbols used herein are as follows.

[0016] (1) Refractive index (nx, ny and nz)

[0017] “nx” represents the refractive index in the direction of maximum in-plane refractive index (i.e., slow axis direction), “ny” represents the refractive index in the direction perpendicular to the slow axis in the plane (i.e., fast axis direction), and “nz” represents the refractive index in the thickness direction.

[0018] (2) In-plane retardation (Re)

[0019] "Re(λ)" refers to the in-plane retardation of a film measured with light having a wavelength of λ nm at 23° C. For example, "Re(550)" refers to the in-plane retardation of a film measured with light having a wavelength of 550 nm at 23° C. When the thickness of the film is represented by "d" (nm), Re(λ) is determined by the equation "Re=(nx-ny)×d".

[0020] (3) Thickness direction retardation (Rth)

[0021] "Rth(λ)" refers to the thickness direction retardation of the film measured at 23°C using light having a wavelength of λnm. For example, "Rth(550)" refers to the thickness direction retardation of the film measured at 23°C using light having a wavelength of 550nm. When the thickness of the film is represented by "d" (nm), rth(λ) is determined by the equation "Rth = (nx-nz) × d".

[0022] (4) Nz coefficient

[0023] The Nz coefficient is determined according to the equation "Nz = Rth / Re".

[0024] (5) Angle

[0025] When an angle is mentioned herein, the angle includes angles in both the clockwise and counterclockwise directions unless otherwise specified.

[0026] A. Optical laminate

[0027] Figure 1 1 is a schematic cross-sectional view of an optical stack according to at least one embodiment of the present invention. Figure 1 The polarizing plate 10, the first retardation layer 21, the second retardation layer 22, and the pressure-sensitive adhesive layer 30 are included in the stated order from the upper side thereof. Figure 1 The upper side corresponds to the observer side, and Figure 1 The lower side corresponds to the image display panel side. The optical laminate can be bonded to the image display panel via a pressure-sensitive adhesive layer 30. The polarizer 10 includes: a polarizer 11; and a protective layer 12 arranged on one side of the polarizer 11 (in the example shown, the observer side). The polarizer of the example shown is a so-called single-sided protected polarizer. Another protective layer (inner protective layer: Depending on the purpose, the polarizer 11 can be arranged on the side opposite to the protective layer 12. That is, the polarizer can be a double-sided protected polarizer. From the point of view of thinning the optical laminate, the inner protective layer can be omitted.

[0028] The first retardation layer 21 and the second retardation layer 22 are each a liquid crystal alignment fixing layer. When the liquid crystal alignment fixing layer is used as a retardation layer, the desired in-plane retardation can be achieved with a thickness much smaller than that of a stretched film of a resin film. As a result, significant thinning of the optical laminate can be achieved. The first retardation layer 21 and the second retardation layer 22 generally have a circular polarization function or an elliptical polarization function, and the relationship of Re(450)<Re(550)<Re(650) holds for their laminate. That is, the first retardation layer 21 and the second retardation layer 22 typically exhibit such reverse wavelength dispersion dependence that their retardation values increase as the wavelength of the measurement light as their laminate increases. With this structure, a satisfactory antireflection function can be achieved in a very wide wavelength band. As used herein, the term "liquid crystal alignment fixing layer" refers to the following layer: a liquid crystal compound is aligned in a predetermined direction in the layer, and its alignment state is fixed. The term "liquid crystal alignment fixing layer" is a concept including an alignment cured layer obtained by curing a liquid crystal monomer.

[0029] In at least one embodiment of the present invention, the thickness T of the polarizer 11 and the storage elastic modulus E of the pressure-sensitive adhesive layer 30 satisfy the following relationship:

[0030] T / E≤0.100 (μm / kPa).

[0031] With this configuration, when the optical laminate is applied to an image display device, display unevenness in a high-temperature environment can be suppressed. The ratio T / E is preferably 0.090 (μm / kPa) or less, more preferably 0.080 (μm / kPa) or less, still more preferably 0.070 (μm / kPa) or less, and particularly preferably 0.065 (μm / kPa) or less. At the same time, the ratio T / E is preferably 0.015 (μm / kPa) or more, more preferably 0.020 (μm / kPa) or more, still more preferably 0.025 (μm / kPa) or more. The inventors of the present invention have conducted extensive research on the relationship between an optical laminate including a liquid crystal alignment fixing layer and display unevenness of an image display device to which the optical laminate is applied in a high-temperature environment, and as a result, found that the shift of the slow axis of the liquid crystal alignment fixing layer caused by the thermal shrinkage of the polarizer is one of the reasons. In addition, the inventors have repeatedly experimented and made mistakes on methods for solving this problem, and as a result, found that when the thickness of the polarizer and the storage elastic modulus of the pressure-sensitive adhesive layer (pressure-sensitive adhesive for forming) are optimally combined, the shift of the slow axis of the liquid crystal alignment fixing layer can be suppressed, and as a result, display unevenness of the image display device in a high-temperature environment can be suppressed. In addition, the inventors have found that when only one of the thickness of the polarizer or the storage elastic modulus of the pressure-sensitive adhesive layer is adjusted, the desired result cannot be obtained. Therefore, the effect according to at least one embodiment of the present invention is an unexpectedly excellent effect.

[0032] In at least one embodiment of the present invention, the sum of the shrinkage rate in the first direction and the shrinkage rate in the second direction perpendicular to the first direction of the optical laminate after heating at 85°C for 240 hours is preferably 0.80% or less, more preferably 0.75% or less, still more preferably 0.70% or less, and particularly preferably 0.65% or less. At the same time, the sum is preferably 0.30% or higher, more preferably 0.35% or higher, and still more preferably 0.40% or higher. With this construction, the desired ratio T / E can be easily achieved. After heating at 85°C for 240 hours, the difference (absolute value) between the shrinkage rate in the first direction and the shrinkage rate in the second direction of the optical laminate is preferably as small as possible. The difference (absolute value) can be, for example, 0.08% or less, can be, for example, 0.07% or less, or can be, for example, zero. With such a configuration, the effect according to at least one embodiment of the present invention can be significant. The first direction may be the absorption axis direction of the polarizer, may be the transmission axis direction of the polarizer, or may be a direction having a predetermined angle (eg, 45° or 135°) with respect to the absorption axis of the polarizer.

[0033] In at least one embodiment of the present invention, the optical laminate may further include a third retardation layer (not shown) between the polarizer 10 and the pressure-sensitive adhesive layer 30. The third retardation layer generally has a refractive index characteristic showing a relationship of nz>nx=ny. When such a third retardation layer is provided, reflection in an inclined direction can be satisfactorily prevented, and an anti-reflection function can be exhibited over a wide viewing angle. The third retardation layer may generally be provided between the second retardation layer 22 and the pressure-sensitive adhesive layer 30.

[0034] In actual use, it is preferred that a release liner is temporarily bonded to the surface of the pressure-sensitive adhesive layer 30 until the optical laminate is used. When the release liner is temporarily bonded, the pressure-sensitive adhesive layer can be protected, and the optical laminate can be formed into a roll shape.

[0035] The structural elements of the optical layered body are specifically as follows.

[0036] B. Polarizer

[0037] B-1. Polarizer

[0038] The polarizer 11 is generally formed of a polyvinyl alcohol (PVA)-based resin film containing a dichroic substance such as iodine. Examples of the PVA-based resin include polyvinyl alcohol, partially fixed polyvinyl alcohol, vinyl alcohol copolymers, and partially saponified products based on ethylene-vinyl acetate copolymers.

[0039] The resin based on PVA preferably includes the resin based on PVA modified by acetoacetyl. Utilize this structure, can obtain the polarizer with required mechanical strength. When the total amount of the resin based on PVA is limited to 100wt%, the blending amount of the resin based on acetoacetyl modified PVA is preferably 5wt% to 20wt%, more preferably 8wt% to 12wt%. When the blending amount falls within such a range, there is a polarizer with more excellent mechanical strength.

[0040] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as "halide"). Examples of iodides include potassium iodide, sodium iodide and lithium iodide. The content of halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of PVA-based resin. In the manufacturing method described later, the halide is mixed into a coating liquid for forming a PVA-based resin layer used as a precursor of the polarizer, and can be finally introduced into the polarizer. When the halide is introduced into the polarizer, the orientation properties of the PVA molecules in the polarizer can be improved, and thus a polarizer with excellent optical properties (usually, high polarization degree and high single-layer transmittance are obtained at the same time) can be obtained.

[0041] The polarizer preferably exhibits absorption dichroism at any wavelength within the wavelength range of 380nm to 780nm. The monolayer transmittance of the polarizer is preferably 41.0% to 46.0%, more preferably 42.0% to 45.0%. The polarization degree of the polarizer is preferably 97.0% or higher, more preferably 99.0% or higher, and even more preferably 99.9% or higher. According to at least one embodiment of the present invention, even when the monolayer transmittance falls within the above range, the polarization degree can be maintained within such a range.

[0042] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. The combination of such a thin polarizer and a liquid crystal orientation fixing layer allows the optical laminate to be significantly thinned. In addition, when the thickness of the polarizer falls within the above range, its curling when heated can be satisfactorily suppressed, and its satisfactory appearance durability when heated can be obtained.

[0043] The polarizer can be produced by any appropriate method. For example, the resin film used to form the polarizer may be a single-layer resin film or may be a laminate of two or more layers.

[0044] Specific examples of the polarizer formed of a single-layer resin film include hydrophilic polymer films such as PVA-based films, partially formalized PVA-based films, and partially saponified films based on ethylene-vinyl acetate copolymers, which have been dyed and stretched with a dichroic substance such as iodine or a dichroic dye, and polyene-based oriented films such as a dehydrated product of PVA and a dehydrochlorinated product of polyvinyl chloride. It is preferred to use a polarizer obtained by dyeing a PVA-based film with iodine and uniaxially stretching it because such a polarizer has excellent optical characteristics.

[0045] Iodine dyeing is performed by, for example, immersing the film based on PVA in an aqueous solution of iodine. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. Stretching can be performed after the dyeing process, or can be performed while dyeing. In addition, dyeing can be performed after stretching. As required, swelling treatment, cross-linking treatment, washing treatment, drying treatment, etc. are performed to the film based on PVA. For example, when washing the film based on PVA with water by immersing in water before dyeing, pollutants and anti-blocking agents on the film surface based on PVA can be washed off, and in addition, the film based on PVA can be swollen to prevent uneven dyeing, etc.

[0046] A specific example of a polarizer obtained by using a laminate is a laminate using a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate or a laminate of a resin substrate and a PVA-based resin layer formed by coating on a resin substrate. The polarizer obtained by using a resin substrate and a laminate of a PVA-based resin layer formed by coating on a resin substrate can be prepared, for example, by applying a PVA-based resin solution to a resin substrate; drying the solution to form a PVA-based resin layer on a resin substrate, thereby providing a laminate of a resin substrate and a PVA-based resin layer; and stretching and dyeing the laminate to convert the PVA-based resin layer into a polarizer. In at least one embodiment of the present invention, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching generally includes stretching the laminate in a state where the laminate is immersed in a boric acid aqueous solution. In addition, stretching may also include stretching the laminate in air at a high temperature (e.g., 95° C. or higher) before stretching in a boric acid aqueous solution as required. In addition, in at least one embodiment of the present invention, it is preferred to subject the laminate to a drying shrinkage treatment, which includes heating the laminate while conveying the laminate in its length direction to shrink the laminate by 2% or more in its width direction. The production method of at least one embodiment of the present invention typically includes subjecting the laminate to an auxiliary stretching treatment in air, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in the order described. When the auxiliary stretching is introduced, the crystallinity of the PVA can be improved even when the PVA is applied to the thermoplastic resin, and thus high optical properties can be achieved. In addition, when the orientation properties of the PVA are improved in advance while the crystallinity is improved, when the laminate is immersed in water in a subsequent dyeing step or a stretching step, problems such as a decrease in the orientation properties of the PVA and its dissolution can be prevented, and thus high optical properties can be achieved. In addition, compared with the case where the PVA-based resin layer does not contain any halide, the interference with the orientation of the polyvinyl alcohol molecules and the decrease in their orientation properties can be suppressed. Therefore, the optical properties of the polarizer obtained by the treatment step (e.g., dyeing treatment and underwater stretching treatment) carried out by immersing the laminate in a liquid can be improved. In addition, the optical properties can be improved by shrinking the laminate in its width direction through a drying shrinkage treatment. The laminate of the resulting resin substrate and polarizer can be used as it is (i.e., the resin substrate can be used as a protective layer of the polarizer), or can be used by laminating any suitable protective layer on the peeling surface from which the resin substrate has been peeled off the laminate of the resin substrate and the polarizer, or laminating on the surface on the opposite side of the peeling surface according to the purpose.Details on such a method of producing a polarizer are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455, the descriptions of which are incorporated herein by reference in their entirety.

[0047] B-2. Protective layer

[0048] The protective layer 12 and the inner protective layer (if present) are each formed of any appropriate resin film. The material used to form the resin film is typically, for example, a cellulose-based resin (such as triacetyl cellulose (TAC)), a cycloolefin-based resin (such as polynorbornene), a (meth) acrylic resin, a polyester-based resin (such as polyethylene terephthalate (PET) or polyethylene naphthalate (PEN)), a polyolefin-based resin (such as polyethylene) or a polycarbonate-based resin. A typical example of a (meth) acrylic resin is a (meth) acrylic resin having a lactone ring structure. The (meth) acrylic resin having a lactone ring structure is described in, for example, Japanese Patent Application Laid-Open No. 2000-230016, Japanese Patent Application Laid-Open No. 2001-151814, Japanese Patent Application Laid-Open No. 2002-120326, Japanese Patent Application Laid-Open No. 2002-254544 and Japanese Patent Application Laid-Open No. 2005-146084, which are incorporated herein by reference. Among them, from the viewpoint of being easy to process into an irregular shape, for example, a cellulose-based resin is preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low moisture permeability and excellent durability, a cycloolefin resin and a (meth) acrylic resin are preferred.

[0049] The optical stack is usually arranged on the observer side of the image display device, and the protective layer 12 is usually arranged on the observer side thereof. Therefore, the protective layer 12 needs to be surface treated as needed. Examples of surface treatment include hard coating treatment, anti-reflection treatment, anti-sticking treatment and anti-glare treatment. In addition / alternatively, when viewed through paired polarized sunglasses (usually imparting circular (elliptical) polarization function or imparting ultra-high delay), the protective layer 12 can be treated as needed to improve visibility. When such treatment is performed, excellent visibility can be achieved even when viewing the display screen through a polarized lens such as a paired polarized sunglasses. Therefore, the optical stack can even be suitably applied to an image display device that can be used outdoors.

[0050] In at least one embodiment of the present invention, it is preferred that the inner protective layer (if present) is optically isotropic. As used herein, the phrase "optically isotropic" means that the layer has an in-plane retardation Re(550) of 0nm to 10nm and a thickness direction retardation Rth(550) of -10nm to +10nm.

[0051] The thickness of the protective layer 12 and the inner protective layer (if present) is preferably 10 to 80 μm, more preferably 12 to 40 μm, and still more preferably 15 to 35 μm. When the protective layer 12 is surface treated, the thickness of the protective layer 12 is a thickness including the thickness of its surface treated layer.

[0052] C. First delay layer and second delay layer

[0053] As described above, both the first retardation layer 21 and the second retardation layer 22 are liquid crystal alignment fixing layers. When the first retardation layer 21 and the second retardation layer 22 are collectively described in this section, they are simply described as "retardation layers" or "liquid crystal alignment fixing layers".

[0054] Examples of liquid crystal compounds for liquid crystal orientation fixed layers include liquid crystal polymers and liquid crystal monomers. Liquid crystal compounds are preferably polymerizable (i.e., liquid crystal monomers). When liquid crystal compounds are polymerizable, the arrangement state of the molecules of the liquid crystal compounds can be fixed by arranging the molecules of the liquid crystal compounds and then polymerizing the compounds. In this case, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal orientation fixed layer does not experience, for example, a transition to a liquid crystal phase, a glass phase, or a crystalline phase caused by temperature changes, which are peculiar to liquid crystal compounds. As a result, the liquid crystal orientation fixed layer becomes a delay layer with excellent stability and is not affected by temperature changes.

[0055] In at least one embodiment of the present invention, the liquid crystal orientation fixing layer can be formed by using a composition containing a polymerizable liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer). Herein, the "polymerizable liquid crystal compound" in the composition refers to a compound having a polymerizable group and having liquid crystal properties. A polymerizable group refers to a group that participates in a polymerization reaction, and is preferably a photopolymerizable group. Herein, a "photopolymerizable group" refers to a group that can participate in a polymerization reaction by, for example, an active free radical or acid generated by a photopolymerization initiator. For example, as described in Japanese Patent Translation Publication No. 2002-533742 (WO 00 / 37585A1), European Patent No. 358208 (U.S. Patent No. 5211877), European Patent No. 66137 (U.S. Patent No. 4388453), WO 93 / 22397A1, European Patent Application Publication No. 0261712, German Patent Application Publication No. 19504224, German Patent Application Publication No. 4408171, British Patent No. 2280445, etc., each can be used as a liquid crystal monomer. Specific examples of such polymerizable mesogen compounds include products available under the product name LC242 from BASF SE, products available under the product name E7 from Merck KGaA, and products available under the product name LC-Sillicon-CC3767 from Wacker Chemie AG.

[0056] The expression mechanism of the liquid crystal properties of the liquid crystal compound may be thermotropic or lyotropic. In addition, the structure of the liquid crystal phase may be nematic liquid crystal or smectic liquid crystal. From the viewpoint of easy production, nematic liquid crystal having thermotropic liquid crystal properties is preferred.

[0057] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its kind. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.

[0058] The birefringence Δn of the liquid crystal orientation fixing layer is preferably 0.06 or more, more preferably 0.08 or more, further preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn may be, for example, 0.13, or may be, for example, 0.12. When Δn falls within such a range, the desired in-plane delay can be achieved with an extremely small thickness. As a result, the thickness of each of the liquid crystal orientation fixing layer and the optical laminate can be further reduced, and thus can ultimately contribute to the significant thinning of the image display device.

[0059] The liquid crystal alignment fixing layer can exhibit such reverse wavelength dispersion characteristics that its retardation value increases as the wavelength of the measurement light increases, such positive wavelength dispersion characteristics that the retardation value decreases as the wavelength of the measurement light increases, or such flat wavelength dispersion characteristics that the retardation value remains substantially unchanged even when the wavelength of the measurement light changes.

[0060] The liquid crystal alignment fixing layer generally has a refractive index characteristic showing the relationship of nx > ny = nz. Therefore, the liquid crystal alignment fixing layer has a slow axis. The equation "ny = nz" includes not only the case where ny and nz are exactly equal to each other, but also the case where ny and nz are substantially equal to each other. Therefore, ny > nz or ny < nz can be adopted to the extent that the effects of the present invention are not impaired.

[0061] The first retardation layer 21 can generally be used as a λ / 2 plate, and the second retardation layer 22 can generally be used as a λ / 4 plate. Specifically, Re(550) of the first retardation layer is preferably from 200 nm to 300 nm, more preferably from 230 nm to 290 nm, still more preferably from 250 nm to 280 nm, and Re(550) of the second retardation layer is preferably from 100 nm to 190 nm, more preferably from 120 nm to 170 nm, still more preferably from 130 nm to 150 nm. The thickness of the first retardation layer can be adjusted so that the in-plane retardation of the desired λ / 2 plate can be obtained. Specifically, the thickness of the layer can be, for example, from 2.0 μm to 4.0 μm. The thickness of the second retardation layer can be adjusted so that the in-plane retardation of the required λ / 4 plate can be obtained. Specifically, the thickness of the layer can be, for example, from 1.0 μm to 2.5 μm. The angle formed by the slow axis of the first retardation layer and the absorption axis of the polarizer is preferably from 10° to 20°, more preferably from 12° to 18°, still more preferably from 14° to 16°, and the angle formed by the slow axis of the second retardation layer and the absorption axis of the polarizer is preferably from 70° to 80°, more preferably from 72° to 78°, still more preferably from 74° to 76°. The arrangement order of the first retardation layer and the second retardation layer can be reversed, and the angle formed by the slow axis of the first retardation layer and the absorption axis of the polarizer and the angle formed by the slow axis of the second retardation layer and the absorption axis of the polarizer can be reversed.

[0062] As described above, the first retardation layer 21 and the second retardation layer 22 have a circular polarization function or an elliptical polarization function, and their laminate has the relationship of Re(450) < Re(550) < Re(650). That is, the laminate of the first retardation layer 21 and the second retardation layer 22 can be used as a λ / 4 plate showing reverse wavelength dispersion dependence. Therefore, in at least one embodiment of the present invention, the laminate of the first retardation layer 21 and the second retardation layer 22 can be replaced by a single retardation layer (liquid crystal alignment fixing layer) that can be used as a λ / 4 plate showing reverse wavelength dispersion dependence.

[0063] The single retardation layer (liquid crystal alignment fixing layer) is formed by using, for example, a composition containing a liquid crystal compound represented by the following formula (I).

[0064] L 1 -SP 1 -A 1 -D 3 -G 1 -D 1 -Ar-D 2 -G 2 -D 4 -A 2 -SP 2 -L 2 (I)

[0065] L 1 and L 2 Each independently represents a monovalent organic group, and L 1 or L 2 At least one of represents a polymerizable group. The monovalent organic group includes any suitable group. 1 or L 2 An example of a polymerizable group represented by at least one of the following is a free radical polymerizable group (a group capable of free radical polymerization). Any suitable free radical polymerizable group can be used as a free radical polymerizable group. The free radical polymerizable group is preferably an acryloyl group or a methacryloyl group. Acryloyl has a high polymerization rate and is therefore preferred from the viewpoint of increasing productivity. Methacryloyl can be similarly used as a polymerizable group of a high birefringence liquid crystal.

[0066] SP 1 and SP 2 Each independently represents a single bond, a straight or branched alkylene group, or a divalent linking group obtained by substituting one or more of the -CH2- moieties of a straight or branched alkylene group having 1 to 14 carbon atoms with -O-. Preferred examples of the straight or branched alkylene group having 1 to 14 carbon atoms include methylene, ethylene, propylene, butylene, pentylene, and hexylene.

[0067] A 1 and A 2 Each independently represents an alicyclic hydrocarbon group or an aromatic ring substituent. 1 and A 2 Each preferably represents an aromatic ring substituent having 6 or more carbon atoms or a cycloalkylene ring having 6 or more carbon atoms.

[0068] D 1 , D 2 , D 3 and D 4 Each independently represents a single bond or a divalent linking group.1 , D 2 , D 3 and D 4 Each represents a single bond, -O-CO-, -C(=S)O-, -CR 1 R 2 -、-CR 1 R 2 -CR 3 R 4 -、-O-CR 1 R 2 -、-CR 1 R 2 -O-CR 3 R 4 -、-CO-O-CR 1 R 2 -、-O-CO-CR 1 R 2 -、-CR 1 R 2 -O-CO-CR 3 R 4 -、-CR 1 R 2 -CO-O-CR 3 R 4 -、-NR 1 -CR 2 R 3 -or-CO-NR 1 -, condition is D 1 , D 2 , D 3 or D 4 At least one of represents -O-CO-. In particular, D 3 Preferably represents -O-CO-, and D 3 and D 4 Each preferably represents -O-CO-. 1 and D 2 Each preferably represents a single bond. 1 , R 2 , R 3 and R 4 Each independently represents a hydrogen atom, a fluorine atom or an alkyl group having 1 to 4 carbon atoms.

[0069] G 1 and G 2 Each independently represents a single bond or an alicyclic hydrocarbon group. 1 and G 2 Each of G and G may represent an unsubstituted or substituted divalent alicyclic hydrocarbon group having 5 to 8 carbon atoms. In addition, one or more -CH2- moieties of the alicyclic hydrocarbon group may be substituted by -O-, -S- or -NH-.1 and G 2 Each preferably represents a single bond.

[0070] Ar represents an aromatic hydrocarbon ring or an aromatic heterocyclic ring. Ar represents an aromatic ring selected from the group consisting of groups represented by the following formulae (Ar-1) to (Ar-6). In the following formulae (Ar-1) to (Ar-6), *1 represents a 1 The bonding position of D 2 bonding position.

[0071]

[0072] In the formula (Ar-1), Q 1 Indicates N or CH, Q 2 Indicates -S-, -O- or -N(R 5 )-. R 5 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. 1 represents an unsubstituted or substituted aromatic hydrocarbon group having 6 to 12 carbon atoms or an aromatic heterocyclic group having 3 to 12 carbon atoms.

[0073] In the formulas (Ar-1) to (Ar-6), Z 1 , Z 2 and Z 3 each independently represents a hydrogen atom, a monovalent aliphatic hydrocarbon group having 1 to 20 carbon atoms, a monovalent alicyclic hydrocarbon group having 3 to 20 carbon atoms, a monovalent aromatic hydrocarbon group having 6 to 20 carbon atoms, a halogen atom, a cyano group, a nitro group, -NR 6 R 7 or -SR 8 . R 6 To R 8 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and Z 1 and Z 2 They may be bonded to each other to form a ring. The ring may be any of an alicyclic ring, a heterocyclic ring and an aromatic ring, and is preferably an aromatic ring. The formed ring may be substituted with a substituent.

[0074] In formulas (Ar-2) and (Ar-3), A 3 and A 4 Each independently represents a group selected from the following: -O-; -N(R 9 )-; -S-; and -CO-, and R 9 represents a hydrogen atom or a substituent. 9 Examples of the substituent represented by include Y in the formula (Ar-1): 1 The substituents which may have are the same as those of the substituents.

[0075] In the formula (Ar-2), X represents a hydrogen atom or an unsubstituted or substituted Group 14 to 16 non-metal atom. Examples of the Group 14 to 16 non-metal atom represented by X include an oxygen atom, a sulfur atom, an unsubstituted or substituted nitrogen atom, and an unsubstituted or substituted carbon atom. Examples of the substituent include the same as Y in the formula (Ar-1). 1 The substituents which may have are the same as those of the substituents.

[0076] In the formula (Ar-3), D 5 and D 6 Each independently represents a single bond, -O-CO-, -C(=S)O-, -CR 1 R 2 -、-CR 1 R 2 -CR 3 R 4 -、-O-CR 1 R 2 -、-CR 1 R 2 -O-CR 3 R 4 -、-CO-O-CR 1 R 2 -、-O-CO-CR 1 R 2 -、-CR 1 R 2 -O-CO-CR 3 R 4 -、-CR 1 R 2 -CO-O-CR 3 R 4 -、-NR 1 -CR 2 R 3 -, or -CO-NR 1 -. R 1 , R 2 , R 3 and R 4 As mentioned above.

[0077] In formula (Ar-3), SP 3 and SP 4 Each independently represents a single bond, a straight chain or branched alkylene group having 1 to 12 carbon atoms, or a divalent linking group obtained by substituting one or more of the parts of the straight chain or branched alkylene group having 1 to 12 carbon atoms with -O-, -S-, -NH-, -N(Q)-, or -CO-, and Q represents a polymerizable group.

[0078] In the formula (Ar-3), L 3 and L 4 Each independently represents a monovalent organic group, and L in formula (1) 3 or L 4 , or L 1 or L 2 At least one of represents a polymerizable group.

[0079] In formulae (Ar-4) to (Ar-6), Ax represents an organic group having 2 to 30 carbon atoms, the organic group having at least one aromatic ring selected from the group consisting of an aromatic hydrocarbon ring; and an aromatic heterocyclic ring. In formulae (Ar-4) to (Ar-6), Ax preferably has an aromatic heterocyclic ring, and more preferably has a benzothiazole ring. In formulae (Ar-4) to (Ar-6), Ay represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms which may be unsubstituted or have a substituent, or an organic group having 2 to 30 carbon atoms, the organic group having at least one aromatic ring selected from the group consisting of an aromatic hydrocarbon ring; and an aromatic heterocyclic ring. In formulae (Ar-4) to (Ar-6), Ay preferably represents a hydrogen atom.

[0080] In formulas (Ar-4) to (Ar-6), Q 3 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may be unsubstituted or substituted. 3 Preferably it represents a hydrogen atom.

[0081] Among such Ar, a group (atomic group) represented by the formula (Ar-4) or the formula (Ar-6) is a preferred example.

[0082] The liquid crystal compound may be used alone or in combination. Specific examples of the liquid crystal compound are described in, for example, Japanese Patent Application Laid-Open No. 2006-163343, Japanese Patent Application Laid-Open No. 2006-178389, and WO 2018 / 123551 A1, the descriptions of which are incorporated herein by reference.

[0083] D. Third delay layer

[0084] The third retardation layer has a refractive index characteristic showing the relationship of nz>nx=ny as described above. That is, the third retardation layer is a so-called positive C plate. The thickness direction retardation Rth(550) of the third retardation layer is preferably -50nm to -300nm, more preferably -70nm to -250nm, still more preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx=ny" includes not only the case where nx and ny are exactly equal to each other, but also the case where nx and ny are substantially equal to each other. That is, the in-plane retardation Re(550) of the third retardation layer can be less than 10nm.

[0085] The third delay layer can be formed of any suitable material. The third delay layer is preferably formed of a film containing a liquid crystal material fixed in a vertical orientation. The vertically oriented liquid crystal material (liquid crystal compound) can be a liquid crystal monomer or a liquid crystal polymer. The liquid crystal compound and the method for forming the delay layer are specifically, for example, the liquid crystal compound and the method for forming the delay layer as described in paragraphs to of Japanese Patent Application Laid-Open No. 2002-333642. In this case, the thickness of the third delay layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.

[0086] E. Pressure-sensitive adhesive layer

[0087] E-1. Overview of pressure-sensitive adhesive layer

[0088] The storage elastic modulus of the pressure-sensitive adhesive layer 30 (basically, the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer) at 25° C. is preferably 70 kPa or more, more preferably 75 kPa to 200 kPa, and still more preferably 80 kPa to 150 kPa. When the storage elastic modulus of the pressure-sensitive adhesive layer under room temperature environment falls within this range, a desired ratio T / E can be easily achieved.

[0089] The storage elastic modulus of the pressure-sensitive adhesive layer (basically, the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer) at 85° C. is preferably 40 kPa or more, more preferably 45 kPa to 500 kPa, and still more preferably 50 kPa to 470 kPa. When the storage elastic modulus of the pressure-sensitive adhesive layer at high temperature falls within such a range, an optical laminate can be obtained that can more satisfactorily suppress display unevenness under a high temperature environment when applied to an image display device.

[0090] The creep value of the pressure-sensitive adhesive layer (basically, the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer) at 23°C is preferably 200 μm or less, more preferably 5 μm to 150 μm, and even more preferably 10 μm to 100 μm. When the creep value of the pressure-sensitive adhesive layer falls within such a range, the desired storage elastic modulus can be easily achieved. The creep value can be measured by, for example, the following procedure: a test sample cut out from a pressure-sensitive adhesive sheet is bonded to a support plate in a 10 mm × 10 mm bonding surface; in a state where the support plate to which the test sample is fixed is fixed, a load of 500 gf is applied vertically downward thereto; the displacement from the support plate after 1 second from the application of the load and after 3600 seconds from the application of the load is measured, and the displacements are calculated by Cr1 and Cr2, respectively. 3600 Indicated by Cr1 and Cr 3600ΔCr determined by the following formula is defined as a creep value. As used herein, the "creep value" refers to a value obtained by converting the thickness of the pressure-sensitive adhesive layer into 20 μm.

[0091] ΔCr=Cr 3600 -Cr1

[0092] The thickness of the pressure-sensitive adhesive layer is preferably 10 μm to 50 μm, more preferably 15 μm to 40 μm. When the thickness of the pressure-sensitive adhesive layer falls within such a range, an optical laminate that can suppress display unevenness in a high temperature environment when applied to an image display device can be realized through the synergistic effect of the optimization effect of the contrast ratio T / E.

[0093] For the pressure-sensitive adhesive layer, any suitable configuration may be adopted as long as the desired ratio T / E can be achieved. The pressure-sensitive adhesive layer required for at least one embodiment of the present invention can be obtained by adjusting, for example, the composition of the pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer (e.g., the kind (polarity, Tg or softness) or molecular weight of the base polymer) or its cross-linking structure (e.g., the kind of cross-linking agent, the distance between cross-linking points (molecular weight between cross-linking points) or cross-linking density).

[0094] E-2. Pressure-sensitive adhesive for forming a pressure-sensitive adhesive layer

[0095] The pressure-sensitive adhesive used to form the pressure-sensitive adhesive layer generally contains a base polymer, a crosslinking agent, and, as necessary, a silane coupling agent and / or additives.

[0096] E-2-1. Base polymer

[0097] The pressure-sensitive adhesive layer is usually formed by a pressure-sensitive adhesive composition comprising a (meth) acrylic polymer, a urethane polymer, a silicone polymer or a rubber polymer as a base polymer. The base polymer is preferably a (meth) acrylic polymer. The (meth) acrylic polymer contains an alkyl (meth) acrylate as a main monomer component. The term "(meth) acrylic acid" refers to acrylic acid and / or methacrylic acid.

[0098] The alkyl (meth)acrylate may be incorporated in a ratio of preferably 50% by weight or more, more preferably 60% by weight or more, still more preferably 70% by weight or more, particularly preferably 80% by weight or more, particularly preferably 90% by weight or more, relative to all monomer components for forming the (meth)acrylic polymer.

[0099] Preferred examples of the alkyl (meth)acrylate are straight or branched alkyl groups having 1 to 18 carbon atoms. The number of carbon atoms of the alkyl group is more preferably 2 to 10, and still more preferably 3 to 8. Examples of the alkyl (meth)acrylate include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, and isooctyl acrylate. The alkyl (meth)acrylate may be used alone or in combination.

[0100] The (meth)acrylic polymer may contain a copolymerizable monomer copolymerizable with the (meth)acrylic acid alkyl ester as a monomer component. Examples of copolymerizable monomers include carboxyl-containing monomers and hydroxyl-containing monomers. A carboxyl-containing monomer is a compound having a carboxyl group in its structure and having a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of carboxyl-containing monomers include (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid and crotonic acid. Among them, acrylic acid is preferred. A hydroxyl-containing monomer is a compound having a hydroxyl group in its structure and having a polymerizable unsaturated double bond such as a (meth)acryloyl group or a vinyl group. Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate and 12-hydroxylauryl (meth)acrylate. Among them, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred. From the viewpoint of adjusting the properties of the pressure-sensitive adhesive layer, copolymerizable monomers different from those described above can be used. Examples of such copolymerizable monomers include amino-containing monomers, amide-containing monomers, multifunctional monomers, cyclizable monomers, sulfonic acid-containing monomers, phosphoric acid-containing monomers, (meth)acrylates with alicyclic hydrocarbon groups, (meth)acrylates with aromatic hydrocarbon groups, vinyl esters, aromatic vinyl compounds, olefins, dienes and vinyl ethers. Copolymerizable monomers can be used alone or in combination.

[0101] E-2-2. Cross-linking agent

[0102] The pressure-sensitive adhesive composition may include a crosslinking agent. For example, an organic crosslinking agent or a multifunctional metal chelate may be used as the crosslinking agent. Examples of organic crosslinking agents include isocyanate-based crosslinking agents, peroxide-based crosslinking agents, epoxy-based crosslinking agents, and imine-based crosslinking agents. The multifunctional metal chelate allows a multivalent metal atom to be covalently bonded or coordinated to an organic compound.

[0103] The blending amount of the crosslinking agent is, for example, 0.01 parts by weight to 5 parts by weight relative to 100 parts by weight of the (meth)acrylic polymer.

[0104] E-2-3. Silane coupling agent

[0105] The pressure-sensitive adhesive composition may include a silane coupling agent. The silane coupling agent preferably has a reactive functional group. The reactive functional group of the silane coupling agent containing the reactive functional group is generally a functional group other than anhydride groups. Examples of functional groups other than anhydride groups include epoxy groups, mercapto groups, amino groups, isocyanate groups, isocyanurate groups, vinyl groups, styryl groups, acetoacetyl groups, urea groups, thiourea groups, (meth) acrylic groups, heterocyclic groups and combinations thereof. The silane coupling agent containing the reactive functional group may be used alone or in combination.

[0106] The blending amount of the reactive functional group-containing silane coupling agent is usually 0.001 to 2 parts by weight relative to 100 parts by weight of the (meth)acrylic polymer.

[0107] E-2-4. Additives

[0108] The pressure-sensitive adhesive composition may include additives. Specific examples of additives include colorants, powders such as pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, antioxidants, anti-aging agents, light stabilizers, ultraviolet absorbers, polymerization inhibitors, inorganic fillers or organic fillers, metal powders, particles and foils. In addition, a redox system obtained by adding a reducing agent can be used to the extent that the composition can be controlled. The type, quantity, combination, content, etc. of the additive can be appropriately set according to the purpose.

[0109] F. Image display device

[0110] The optical laminate described in sections A to E can be applied to an image display device. Therefore, at least one embodiment of the present invention also includes an image display device using such an optical laminate. Typical examples of image display devices include liquid crystal display devices and organic EL display devices. An image display device according to at least one embodiment of the present invention generally includes the optical laminate described in sections A to E on its observer side.

[0111] Example

[0112] The present invention is specifically described below by way of examples. However, the present invention is not limited to these examples. The measurement methods and evaluation methods in the examples are as follows.

[0113] (1) Thickness

[0114] The thickness was measured to be 10 μm or less by an interference film thickness meter (manufactured by Otsuka Electronics Co., Ltd., product name: MCPD-3000). The thickness was measured to be 10 μm or less by a digital micrometer (manufactured by Otsuka Electronics Co., Ltd., product name: KC-351C).

[0115] (2) Storage elastic modulus

[0116] The pressure-sensitive adhesive layer (pressure-sensitive adhesive) used in each of Examples and Comparative Examples was subjected to dynamic viscoelasticity measurement under the conditions indicated below using an "Advanced Rheometric Dilatation System (ARES)" manufactured by Rheometric Scientific, Inc. The storage elastic modulus was read from the measurement results.

[0117] (Measurement conditions)

[0118] Deformation Mode: Distortion

[0119] Measuring temperature: -40℃ to 150℃

[0120] Heating rate: 5℃ / min

[0121] Measuring frequency: 1Hz

[0122] (3) Shrinkage

[0123] The optical laminate obtained in each of the examples and comparative examples was cut into a rectangular shape of 128 mm×160 mm to provide a test sample. For convenience, the test sample was divided into 32 mm 2 The precise dimensions of each area in the long and short directions were measured using the "CNC visual measurement system" manufactured by Mitutoyo, and the average dimensions were expressed as S LS0 and S SS0 After measuring the size, the test sample was heated at 85°C for 240 hours, and the size after heating was similarly measured. The size after heating is represented by S LS1 and S SS1 Indicates. Shrinkage rate S in the long side direction LS By (S LS0 -S LS1 ) / S LS0 ×100. SS0 -S SS1 ) / S SS0 ×100Determine the shrinkage rate S in the short side direction SS .

[0124] (4) Display unevenness

[0125] The optical laminate obtained in each of the examples and comparative examples was bonded to a glass plate via a pressure-sensitive adhesive layer to provide a test sample. The test sample was heated at 85° C. for 500 hours and then mounted on a reflective plate (manufactured by Toray Advanced Film Co., Ltd., product name: "Cerapeel DMS-X42", total light reflectance: 86%). The reflection hue (L*a*b* color system) was measured using CM2600-d (manufactured by Konica Minolta), and the formula (a 2 +b 2 ) 1 / 2 Δab was determined. Display non-uniformity in a high temperature environment was evaluated by the following criteria.

[0126] ○ (good): Δab is less than 1.5.

[0127] Δ(normal): Δab is 1.5 or more and less than 2.5.

[0128] ×(bad): Δab is 2.5 or more.

[0129] [Production Example 1: [Preparation of pressure-sensitive adhesive]

[0130] (Preparation of Acrylic Polymer A1)

[0131] A monomer mixture containing 99 parts of butyl acrylate and 1 part of 4-hydroxybutyl acrylate was charged into a four-necked flask having a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser. In addition, 0.1 parts of 2,2′-azobisisobutyronitrile used as a polymerization initiator was loaded together with 100 parts of ethyl acetate relative to 100 parts of the monomer mixture. While the mixture was gently stirred, nitrogen purging was performed by introducing nitrogen gas. Thereafter, a polymerization reaction was performed for 8 hours while the liquid temperature in the flask was maintained at about 55°C. Thus, a solution of acrylic polymer A1 having a weight average molecular weight (Mw) of 1,800,000 and satisfying Mw / Mn=4.8 was prepared.

[0132] (Preparation of pressure-sensitive adhesive)

[0133] 0.1 parts of a xylylene diisocyanate adduct of trimethylolpropane (manufactured by Tosoh Corporation, product name: “TAKENATE D110N”), 0.3 parts of a peroxide crosslinking agent (manufactured by NOF Corporation, product name: “NYPER BMT”) and 0.2 parts of an epoxy-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name: “KBM-403”) were blended into 100 parts of the solid content of the acrylic polymer A1 solution to provide a pressure-sensitive adhesive PSA1.

[0134] [Production Example 2: [Preparation of pressure-sensitive adhesive]

[0135] (Preparation of Acrylic Polymer A2)

[0136] A monomer mixture containing 94.9 parts of butyl acrylate, 0.1 parts of 2-hydroxyethyl acrylate and 5 parts of acrylic acid was charged into a four-necked flask with a stirring blade, a thermometer, a nitrogen inlet tube and a condenser. In addition, 0.1 parts of 2,2′-azobisisobutyronitrile used as a polymerization initiator was loaded together with 100 parts of ethyl acetate with respect to 100 parts of the monomer mixture. While gently stirring the mixture, nitrogen purging was performed by introducing nitrogen gas. Thereafter, a polymerization reaction was performed for 8 hours while the liquid temperature in the flask was maintained at about 55°C. Thus, a solution of an acrylic polymer A2 having a weight average molecular weight (Mw) of 2,200,000 and satisfying Mw / Mn=3.9 was prepared.

[0137] (Preparation of pressure-sensitive adhesive)

[0138] 0.6 parts of toluene diisocyanate adduct of trimethylolpropane (manufactured by Tosoh Corporation, product name: "CORONATE L"), 0.2 parts of a peroxide crosslinking agent (manufactured by NOF Corporation, product name: "NYPERBMT") and 0.2 parts of an epoxy-containing silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., product name: "KBM-403") are blended into 100 parts of a solid content acrylic polymer A2 solution to provide a pressure-sensitive adhesive PSA2.

[0139] [Production Example 3: [Preparation of pressure-sensitive adhesive]

[0140] (Preparation of prepolymer composition)

[0141] 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (product name: "Omnirad 651", manufactured by IGM Resins BV) used as a first photopolymerization initiator, and 0.05 parts by weight of 1-hydroxycyclohexyl phenyl ketone (product name: "Omnirad 184", manufactured by IGM Resins BV) used as a second photopolymerization initiator were added to a monomer mixture containing 60 parts by weight of n-octyl acrylate (NOAA), 30 parts by weight of butyl acrylate (BA), 8 parts by weight of 4-hydroxybutyl acrylate (4HBA) and 2 parts by weight of N-vinyl-2-pyrrolidone (NVP) in a flask. Thereafter, the monomer components in the mixture were partially polymerized by irradiating the mixture with UV light under a nitrogen atmosphere. Thus, a prepolymer composition having a polymerization ratio of about 10% was obtained.

[0142] (Preparation of pressure-sensitive adhesive)

[0143] 100 parts by weight of the prepolymer composition obtained above, 0.08 parts by weight of dipentaerythritol hexaacrylate (DPHA) as a crosslinking agent, 0.05 parts by weight of 2,2-dimethoxy-1,2-diphenyl-1-one (product name: "Omnirad 651", manufactured by IGM Resins BV) used as a photopolymerization initiator, and 0.3 parts by weight of a silane coupling agent (product name: "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to provide a pressure-sensitive adhesive PSA3.

[0144] [Production Example 4: [Production of polarizing plate]

[0145] 1. Production of polarizer

[0146] An amorphous isophthalic acid copolymerized polyethylene terephthalate film (thickness: 100 μm) having an elongated shape and having a Tg of about 75° C. was used as a thermoplastic resin substrate, and one surface of the resin substrate was subjected to a corona treatment.

[0147] A PVA aqueous solution (coating liquid) was prepared by dissolving a product obtained by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree: 4,200, saponification degree: 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name: "GOHSEFIMER") in water.

[0148] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm. Thus, a laminate was produced.

[0149] The obtained laminate was uniaxially stretched at a ratio of 2.4 times in its longitudinal direction (length direction) in an oven at 130° C. (auxiliary stretching treatment in air).

[0150] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 100 parts by weight of water with 4 parts by weight of boric acid) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0151] Next, the laminate is immersed in a dyeing bath (an aqueous solution of iodine obtained by blending 100 parts by weight of water with iodine and potassium iodide in a weight ratio of 1:7) having a liquid temperature of 30°C for 60 seconds, while adjusting the concentration of the aqueous solution so that the single-layer transmittance (Ts) of the polarizer finally obtained becomes the desired value (dyeing treatment).

[0152] Next, the laminate was immersed in a crosslinking bath (boric acid aqueous solution obtained by blending 100 parts by weight of water with 3 parts by weight of potassium iodide and 5 parts by weight of boric acid) having a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0153] Thereafter, while the stack is immersed in an aqueous boric acid solution at a liquid temperature of 70°C (boric acid concentration: 4 wt%, potassium iodide concentration: 5 wt%), the stack is uniaxially stretched in the longitudinal direction (length direction) between rollers with different circumferential speeds so that the total stretching ratio becomes 5.5 times (underwater stretching treatment).

[0154] Thereafter, the laminated body was immersed in a washing bath (an aqueous solution obtained by blending 100 parts by weight of water with 4 parts by weight of potassium iodide) having a liquid temperature of 20° C. (washing treatment).

[0155] Thereafter, the laminate was dried in an oven maintained at approximately 90°C while being brought into contact with a heating roller made of SUS whose surface temperature was maintained at approximately 75°C (drying shrinkage treatment).

[0156] Thus, a polarizing plate having a thickness of about 5 μm was formed on the resin substrate to provide a polarizer having a “resin substrate / polarizing plate” configuration. The single-layer transmittance Ts of the polarizer was 43.3%.

[0157] 2. Production of polarizers

[0158] A biaxially stretched acrylic resin film (thickness: 20 μm) was bonded to the surface of the obtained polarizer (its surface was on the side opposite to the resin substrate) via a UV-curable adhesive. Next, the resin substrate was peeled off. Thus, a polarizing plate P1 having a "biaxially stretched acrylic resin film (protective layer) / polarizer" structure was obtained.

[0159] [Production Example 5: [Production of polarizing plate]

[0160] A polarizing plate P2 having a configuration of “unstretched COP film (protective layer) / polarizer” was obtained in the same manner as in Production Example 4 except that an unstretched cycloolefin-based resin (COP) film (thickness: 25 μm) was used instead of the acrylic resin film.

[0161] [Production Example 6: Production of polarizing plate]

[0162] A polarizing plate P3 having a configuration of “obliquely stretched COP film (protective layer) / polarizer” was obtained in the same manner as in Production Example 4 except that an obliquely stretched COP film (thickness: 25 μm) was used instead of the acrylic resin film.

[0163] [Production Example 7: Production of polarizing plate]

[0164] 1. Production of polarizer

[0165] A polyvinyl alcohol (PVA)-based resin film (manufactured by Kurara Corporation, product name: "PE3000") having a thickness of 30 μm was uniaxially stretched along its length direction using a roll stretching machine so that the total stretching ratio became 5.9 times. While being stretched, the film was subjected to swelling treatment, dyeing treatment, cross-linking treatment and washing treatment. Finally, the film was dried to prepare a polarizer having a thickness of 12 μm.

[0166] Specifically, in the swelling treatment, the film was stretched at a ratio of 2.2 times while being treated with pure water at 20°C. Next, in the dyeing treatment, the film was stretched at a ratio of 1.4 times while being treated at 30°C in an aqueous solution containing iodine and potassium iodide in a weight ratio of 1:7, the iodine concentration of the aqueous solution being adjusted so that the single-layer transmittance of the polarizer to be obtained becomes 45.0%. In addition, a two-stage crosslinking treatment was adopted as the crosslinking treatment. In the first-stage crosslinking treatment, the film was stretched at a ratio of 1.2 times while being treated at 40°C in an aqueous solution in which boric acid and potassium iodide were dissolved. The boric acid content and potassium iodide content of the aqueous solution of the first-stage crosslinking treatment were set to 5.0wt% and 3.0wt%, respectively. In the second-stage crosslinking treatment, the film was stretched at a ratio of 1.6 times while being treated at 65°C in an aqueous solution in which boric acid and potassium iodide were dissolved. The boric acid content and potassium iodide content of the aqueous solution of the second-stage crosslinking treatment were set to 4.3wt% and 5.0wt%, respectively. Furthermore, in the washing treatment, the film was treated with a potassium iodide aqueous solution at 20° C. The potassium iodide content of the aqueous solution in the washing treatment was set to 2.6 wt %. Finally, in the drying treatment, the film was dried at 70° C. for 5 minutes. Thus, a polarizer was obtained.

[0167] 2. Production of polarizers

[0168] The TAC film (thickness: 25 μm) and the obliquely stretched COP film (thickness: 20 μm) were bonded to both sides of the polarizer by a polyvinyl alcohol-based adhesive. Thus, a polarizing plate P4 having a "TAC film (protective layer) / polarizer / obliquely stretched COP film (protective layer)" structure was obtained.

[0169] [Example 1]

[0170] 1. Production of the first delay layer and the second delay layer

[0171] A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase (manufactured by BASF SE, "Paliocolor LC242", the chemical formula indicated below) was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 20 wt%. A leveling agent (manufactured by DIC, "MEGAFACE F-563"), a photopolymerization initiator (manufactured by IGM Resins BV, "Omnirad 907") and a crosslinking agent (manufactured by Shin-Nakamura Chemical Industry Co., Ltd., "A-DCP") were added to the solution to prepare a coating liquid for forming a liquid crystal orientation fixing layer. A tilted stretched COP film was prepared as a substrate. The above-mentioned coating liquid for forming a liquid crystal orientation fixing layer was applied to the substrate with a spin coater, and heated at 100°C for 3 minutes to orient the liquid crystal compound. The resultant was cooled to room temperature and then irradiated by centrifugation under a nitrogen atmosphere with an integrated irradiance of 600 mJ / cm 2 The UV light was irradiated and photocured to fix the orientation state of the liquid crystal compound. Thus, a laminate having a structure of "substrate / first liquid crystal orientation fixing layer" was obtained (thickness: from 1.5 μm to 2.5 μm, Re (550): 270 nm). A laminate having a structure of "substrate / second liquid crystal orientation fixing layer" was obtained in the same manner as above except that the coating thickness was changed (thickness: from 1.0 μm to 1.5 μm, Re (550): 140).

[0172]

[0173] 2. Production of the third delay layer

[0174] 20 parts by weight of a side chain type liquid crystal polymer represented by the chemical formula indicated below having a weight average molecular weight of 5,000 (n=0.35, and for convenience, the polymer is represented in the form of a block polymer), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF SE: product name: Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals, product name: Irgacure 907) were dissolved in 200 parts by weight of cyclopentanone to prepare a liquid crystal coating liquid. Then, the coating liquid was applied to a PET substrate that had been subjected to a vertical alignment treatment using a rod coater, and then heated and dried at 80°C for 4 minutes to orient its liquid crystal molecules. UV light was applied to the liquid crystal layer to cure the liquid crystal layer. Thus, a positive C plate (thickness: 3 μm) was formed on the substrate.

[0175]

[0176] 3. Manufacturing of optical laminate

[0177] The first retardation layer is bonded to the polarizer surface of the polarizer P1 obtained in Preparation Example 4 via a UV-curable adhesive (thickness: 1 μm), and then the substrate is peeled off. Next, the second retardation layer is bonded to the surface of the first retardation layer via a UV-curable adhesive (thickness: 1 μm), and the substrate is peeled off. Next, the third retardation layer is bonded to the surface of the second retardation layer via a UV-curable adhesive (thickness: 1 μm), and the substrate is peeled off. The pressure-sensitive adhesive PSA1 (thickness: 15 μm) obtained in Preparation Example 1 is arranged on the peeling surface. Thus, an optical laminate having a "polarizer / first retardation layer / second retardation layer / third retardation layer / pressure-sensitive adhesive layer" structure is obtained. The T / E ratio of the obtained optical laminate is 0.062. The obtained optical laminate was evaluated (3) and (4). The results are shown in Table 1.

[0178] [Examples 2 to 6 and Comparative Examples 1 to 6]

[0179] As shown in Table 1, optical laminates were respectively prepared by combining a polarizing plate and a pressure-sensitive adhesive layer. The obtained optical laminates were subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0180] Table 1

[0181]

[0182] In Table 1, for example, the expression "acrylic" means that a protective layer of an acrylic resin film is provided on one side of the polarizer, and the expression "COP / TAC" means that protective layers of a COP film and a TAC film are provided on both sides of the polarizer. In addition, the expression "oblique stretching" below "COP / TAC" means that the COP film is an obliquely stretched film.

[0183] As is apparent from Table 1, according to the embodiments of the present invention, it was found that display unevenness under a high temperature environment was suppressed by optimizing the ratio T / E of the thickness T of the polarizer to the storage elastic modulus E of the pressure-sensitive adhesive layer. In addition, it was found that this effect could not be obtained by adjusting only either the thickness of the polarizer or the storage elastic modulus of the pressure-sensitive adhesive layer.

[0184] The optical laminate according to at least one embodiment of the present invention can be suitably used in an image display device (typically a liquid crystal display device or an organic EL display device).

Claims

1. An optical laminate comprising, in the order described: A polarizing plate including a polarizer; First delay layer; a second delay layer; and a pressure-sensitive adhesive layer, in, The first retardation layer and the second retardation layer are each a liquid crystal alignment fixing layer, and The thickness T of the polarizer and the storage elastic modulus E of the pressure-sensitive adhesive layer satisfy the following relationship: T / E≤0.100(μm / kPa).

2. The optical layered body according to claim 1, wherein: The optical stack has a total shrinkage rate in a first direction and a shrinkage rate in a second direction perpendicular to the first direction after heating at 85° C. for 240 hours of 0.80% or less.

3. The optical layered body according to claim 1, wherein: The storage elastic modulus E of the pressure-sensitive adhesive layer is 70 kPa or more, and / or the thickness T of the polarizer is 8 μm or less.

4. The optical layered body according to claim 1, wherein the first retardation layer has Re (550) of 200 nm to 300 nm, and its slow axis forms an angle of 10° to 20° with the absorption axis of the polarizer, and The second retardation layer has Re (550) of 100 nm to 190 nm, and its slow axis forms an angle of 70° to 80° with the absorption axis of the polarizer. 5 . The optical stack according to claim 1 , further comprising a third retardation layer having a refractive index characteristic showing a relationship of nz>nx=ny between the polarizing plate and the pressure-sensitive adhesive layer. 6 . An image display device comprising the optical layered body according to claim 1 .

Citation Information

Patent Citations

  • Liquid crystalline reticulated polysiloxanes

    EP0066137A1

  • Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer

    EP0261712A1

  • Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups

    EP0358208A2

  • Liquid crystalline copolymer

    GB2280445A

  • Optically active liquid crystal compound having cyano group

    JP1989070455A